La evo-devo como ciencia histórica de causas remotas (2009)
ABSTRACT EVO-DEVO AS HISTORICAL SCIENCE OF ULTIMATES CAUSES Having as starting point that a proximal cause is one which effects can be registered in the states of an individual organism, in this work I will argue that what defines an ultimate cause is the fact that its effects can be registered in the evolution of lineages, and not simply in population states. This, on the other hand, not only will allow us to clarify how the developmental constraints can be understood as causes of the evolutionary phenomena; but also it will allow us to point the eminently historical character of Developmental Evolutionary Biology that Wallace Arthur lessened in Biased Embryos and Evolution. Thus, and following this latter reasoning, I will also try to show that, although the action of developmental constraints could happen beyond the limits of a population or a particular species, that does not imply that we are before a comeback of typological thought in Evolutionary Biology. Key Words: Evolutionary Developmental Biology; Typological Thought; Ultimate Causes.   RESUMEN Partiendo de la premisa de que una causa próxima es aquella cuyos efectos pueden ser registrados en los estados de un organismo individual, en este trabajo sostendré que lo que define a una causa remota es el hecho de que sus efectos puedan ser registrados en la evolución de linajes, y no simplemente en estados poblacionales. Esto, por otra parte, no sólo nos permitirá entender en qué sentido los constreñimientos ontogenéticos deben ser comprendidos como causas remotas de los fenómenos evolutivos; sino que además nos permitirá poner en evidencia el carácter eminentemente histórico de la Biología Evolucionaria del Desarrollo que Wallace Arthur menoscabó en Biased Embryos and Evolution.  Así, y siguiendo esta última línea de razonamiento, también intentaré mostrar que, aunque la acción de dichos constreñimientos ontogenéticos pueda verificarse más allá de los límites de una población o especie particular, eso no implica que estemos asistiendo a un retorno del pensamiento tipológico en Biología Evolucionaria. Palabras Clave: Biología Evolucionaria del Desarrollo; Causas Remotas; Pensamiento Tipológico.